Restorative Practices as a Tool to Affect Peer Influence on Academic Integrity and Misconduct - Sopcak, Paul; Stewart, Alycia (Canadian Perspectives on Academic Integrity, 2021)
Integrity is often related to acting ethically based on intrinsic motivation, rather than external controls. The disconcerting spike in misconduct cases in the pandemic-related, uninvigilated, remote learning environments has made it clear how far away from promoting integrity and its fundamental values (ICAI, 2021) over mere rule compliance we really are. Further, research routinely finds peer influence to be one of the most important factors affecting academic misconduct. Restorative Practices (RP), when applied not only in response to misconduct, but also as an educational and proactive community building tool, have been shown to be an effective way of preventing misconduct by fostering a sense of trust and community. They have further been found to empower marginalized individuals and communities, pursue and demonstrate fairness, as well as foster empathy, compassion, and accountability. Moreover, RP provide a process that enables student engagement and thus an opportunity to engage in peer-to-peer interaction on the topic of academic integrity and misconduct. In our presentation, we will provide a brief introduction to the principles of RP, followed by a discussion of their application to academic integrity and misconduct at MacEwan University, with a particular focus on student engagement and peer to peer interaction.